Inclusion Politics/Subalternization Practices: The Construction of Ethnicity in Villancicos de Negros of the Cathedral of Santiago de Guatemala (16th-18th Centuries) - Singer, Deborah Singer (2019)
This article problematizes the notion of ethnicity underlying villancicos de negros of the Archdiocesan Historical Archive of Guatemala (AHAG). Although these are musical pieces that project the idea of social harmony in a festive context, the truth is that identities emerge in conflict with colonial power, based on an ambivalent discourse that consolidates and naturalizes racial stereotypes.